Firstly, in order to identify a, b and c , we must re-arrange the expression in the proper form ie. all the terms to the left, leaving zero on the right:

`2x^2- 4x - 3 = 0`

Only then, we can see that:

`a = 2`, `b = -4` and `c = -3`

Substituting these into the quadratic formula, we get:

`x=(-b+-sqrt(b^2-4ac))/(2a)`

`x=(-(-4)+-sqrt((-4)^2-4(2)(-3)))/(2(2))`

`=(4+-sqrt(16+24))/4`

`=(4+-sqrt40)/4`

`=(4-sqrt40)/4 or (4+sqrt40)/4`

So

`x=-0.581 or 2.581`

Get the Daily Math Tweet!
IntMath on Twitter